Analisis Dampak Penggunaan Media Sosial Facebook terhadap Akhlak Ibu-Ibu Rumah Tangga di Kampung Durian Kandang - Novella Susanti; AlFurqan AlFurqan (AS-SABIQUN, 2022)
This study aims to find out what are the forms of facebook social media abuse against housewives, how the impact of facebook social media has on the morals of housewives and find out what efforts can be made to avoid facebook social media abuse in Durian Kandang Jorong Sigunanti Village, Kinali District, West Pasaman Regency. This type of research is qualitative research with a case study approach. The main instrument in this study is the researcher himself. Data collection techniques are carried out by means of observation, interviews and documentation. The steps of analyzing data are data reduction, data presentation and drawing conclusions. The results of this study are 1) the form of facebook social media abuse that occurs in Kampung Durian Kandang, namely the first, facebook social media is used as a place to vent, facebook social media is used as a place to satirize each other, and facebook social media is used as a place to show off riya'(show off), 2) the impact of facebook social media on the morals of housewives in Kampung Durian Kandang is, morals in speaking impolite words, indulge in personal things or disgrace through facebook social media, both in terms of household and family privacy, as well as neglect in terms of worshipping Allah SWT, namely the obligation in praying five times, 3) efforts that can be made to avoid misuse of facebook social media in Kampung Durian Kandang is to carry out sports activities, housewives' food and wirid yasin activities are carried out once a week.